Intraoperative frozen sections of the regional lymph nodes contribute to surgical decision-making in non-small cell lung cancer patients - Li, Wei; Yang, Xue-Ning; Liao, Ri-Qiang; Nie, Qiang; Dong, Song; Zhai, Hao-Ran; Wu, Yi-Long; Zhong, Wen-Zhao (Journal of Thoracic Disease, 2016)
Background: Individualization of pulmonary parenchymal resection and lymphadenectomy in lung cancer patients will likely become more important as surgical innovation. This study explored the utility of intraoperative pathological frozen sections of regional lymph nodes in non-small cell lung cancer (NSCLC) patients. Methods: Patients with NSCLC underwent intraoperative sampling of N1 station lymph nodes depending on the location of the tumor, any other suspicious lymph nodes were also biopsied. The contribution of frozen-section analysis to surgical decision-making was evaluated. Results: Of 74 lung cancer patients who underwent intraoperative frozen section analysis of lymph nodes, the positive rate was 18/74 (24.3%). The extents of agreement between preoperative N staging (cN) and intraoperative N staging (sN), cN staging and postoperative N staging (pN), and sN staging and pN staging were 62.2% (46/74), 63.5% (47/74), and 71.6% (53/74), respectively. When frozen section was combined with evaluation of pulmonary function and intrathoracic adhesions, surgical strategies were modified during operations in 18 cases (5 sN-positive, 13 sN-negative). Of these patients, five underwent extensive pulmonary parenchymal resection, and four had conservative lung parenchymal resection. In nine patients, the extent of lymph node dissection (LND) was changed. Conclusions: Intraoperative frozen section of regional lymph nodes led to 24.3% operative strategies modification in lung cancer. Frozen section analysis may make an important contribution to surgical decision-making in terms of pulmonary parenchymal resection and LND.